Coronary Vasculature Development, Structure-Function, and Adaptations - Tomanek, Robert J.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2013)
Ischemic heart disease is the leading cause of morbidity and mortality in the developed world. The high metabolism and oxygen demand of the cardiac myocardium depends on both a high blood flow and a rich capillary density. For this reason, the growth of the coronary vasculature is vital, not only in early development, but also in the adult faced with various stresses. Novel technologies have enabled the discovery of the molecular mechanisms underlying the growth and assembly coronary vessels, and this volume covers the hierarchy of the coronary vasculature from its embryonic origins through its postnatal growth, adulthood, and senescence. Chapters address normal coronary development, coronary anomalies and their possible underlying developmental errors, coronary vessel adaptations to exercise training, aging, hypoxia, myocardial ischemia, and cardiac hypertrophy. This comprehensive overview of current research in coronary vessels and myocardial perfusion was written by Dr. Robert J. Tomanek, Emeritus Professor of Anatomy and Cell Biology at the University of Iowa. The book reviews, discusses, and integrates findings from various areas of coronary vasculature research, and as a result, will be a valuable reference source for cardiovascular scientists and physicians for many years to come.
General concepts of blood vessel formation and remodeling -- Prenatal coronary morphogenesis -- Postnatal coronary morphogenesis and growth -- Structure-function of the coronary hierarchy -- Historical perspectives -- Coronary anomalies -- Aging -- Adaptations to exercise training -- Hypoxia -- Myocardial ischemia and infarction -- Cardiac hypertrophy -- Therapy for coronary circulation.
Keywords: Medicine; Cardiology; Medicine & Public Health; Cardiology; Medicine/Public Health, general; Biomedicine general; Molecular Medicine